Analysis Review of Feature-Based Method in Term of Verification and Validation Performance - Din, Roshidi; Utama, Sunariya (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The categories of information named steganography has become the options of securing hidden message that wouldn’t be detected by intruders or third party. Implementation steganography able to develop in several domains and this paper focuses on text domain of steganography. This paper particularizes the implementation one of the category of steganography in text domain that measures the evaluation performance through verification and validation approaches. It reviews one of the methods in text steganography called feature-based. This method has been established by previous researcher effort that to cover hidden message based on characteristic of letters in the text. This paper identifies the type of measurement that has been used developed as the feature-based method of text steganography. It anticipated the identification of evaluation performance through verification and validation can able to use as procedure the measurement performance in steganography implementation.